Deconstruction of Christianity in the Postmodern Age: What Remains after That? - Jabeen, Asma; Qurrat ul Ain, Ayesha (Journal of Islamic and Religious Studies, 2021)
This article provides an insight into the project of deconstruction of Christianity by applying the interpretation of Derrida’s deconstruction in the language of Christian theology. The focus of this paper is on Caputo’s work, which is known as the leading interpreter of Derrida’s deconstruction. It is explored that how Caputo’s project of deconstruction redefines Christianity and what remains of Christianity after that. This study analyses that the project of Deconstruction of Christianity by Caputo was based on the question that how to talk about God or how to be a Christian in the postmodern age. His response to these basic questions leads to a non-particular and non-theologized form of Christianity, which is not different from other (religions/worldviews), because Christianity which remains after the deconstruction, simply withdraws itself from the exclusivist ways/teachings, and the Bible is not an exception to that. Deconstructed Christianity is a religion, where God is distant, His truth is invasive, and Christian faith is non-particular.